2022
DOI: 10.1051/0004-6361/202243259
|View full text |Cite
|
Sign up to set email alerts
|

The complex time and energy evolution of quasi-periodic eruptions in eRO-QPE1

Abstract: Quasi-periodic eruptions (QPEs) are recurrent X-ray bursts found so far in the nuclei of low-mass galaxies. Their trigger mechanism is still unknown, but recent models involving one or two stellar-mass companions around the central massive (≈ 10 5 − 10 6 M ) black hole have gathered significant attention. While these have been compared only qualitatively with observations, the phenomenology of QPEs is developing at a fast pace, with the potential to reveal new insights. Here we report two new observational res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…• While the case against gravitational lensing, as described by Ingram et al (2021), for the mechanism in QPE sources is strong in light of the asymmetry seen in the eruptions of eRO-QPE1 (Arcodia et al 2022), we can make no similar claim for the variability in 2XJ1231. It does, however, still appear to be an unlikely mechanism, as with GSN 069 and RX J1301.9+2747, as the black hole mass being as low as 10 5 𝑀 would produce eruptions which are either not of a large enough amplitude or not long enough in duration without the inclusion of a complex geometry for the emitting regions.…”
Section: Discussionmentioning
confidence: 88%
“…• While the case against gravitational lensing, as described by Ingram et al (2021), for the mechanism in QPE sources is strong in light of the asymmetry seen in the eruptions of eRO-QPE1 (Arcodia et al 2022), we can make no similar claim for the variability in 2XJ1231. It does, however, still appear to be an unlikely mechanism, as with GSN 069 and RX J1301.9+2747, as the black hole mass being as low as 10 5 𝑀 would produce eruptions which are either not of a large enough amplitude or not long enough in duration without the inclusion of a complex geometry for the emitting regions.…”
Section: Discussionmentioning
confidence: 88%
“…If the heating is strong enough to unbind the gas, the speed of the large-scale eddies is comparable to the escape speed. If, as is commonly the case in turbulent dynamos (Kulsrud & Anderson 1992;Schekochihin et al 2004;Bott et al 2021;Seta & Federrath 2021;Arcodia et al 2022), the magnetic field energy density is amplified to rough equipartition with the turbulent kinetic energy density, the Alfvén speed would then be comparable to the star's escape speed. On the main sequence, this is almost always ;0.002c, or ∼2 × 10 −2 v orb when a ∼ 100r g .…”
Section: Flare Heatingmentioning
confidence: 97%
“…A potential consequence of strong, irregular pressure fluctuations is turbulence. A large body of work on turbulent dynamos (Kulsrud & Anderson 1992;Schekochihin et al 2004;Bott et al 2021;Seta & Federrath 2021;Arcodia et al 2022) has shown that large-amplitude (transonic) turbulence can amplify the magnetic field enough to make the Alfvén speed v A ∼ c s , for c s the local sound speed (in conditions of high opacity like a star, the sound speed reflects the combination of gas and radiation pressure). As the gas being transferred accelerates away from the star (pulled by the black hole's tidal gravity and pushed by its internal pressure gradient), one might expect v A to increase above c s as the gas density drops while the component of the magnetic field parallel to the flow is unchanged.…”
Section: Angular Momentum Transport By Magnetic Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…12). The large variation in flare luminosities, as well as occasional overlapping flares (Arcodia et al 2022), could arise either from variation in the mass stripped from the star in a given orbit and/or variations in the circularization efficiency. Given the complex disk-star interactions ( §4) and stellar debris circularization ( §5), it is natural to expect such variations.…”
Section: Gsn069mentioning
confidence: 99%